Rapid screening of methicillin-resistant Staphylococcus aureus carrying the mecC gene in a Portuguese hospital - Diaz, Raquel (2018)
Background: The discovery of mecC gene in MRSA isolates and its report in neighboring Spain and France, advices for monitoring its presence in Portuguese hospitals since changes in local epidemiology can occur quickly. The implementation of rapid procedures based on the automated system VITEK2 allow for simple screening of mecC MRSA isolates with the profile of susceptibility to oxacillin and resistance to cefoxitin signaling positive results for detailed analysis. Methods: This works aims to perform a retrospective study for the presence of suspect mecC MRSA in a Portuguese hospital recurring to the two methodologies included in microbiology laboratories routine. Result: Our results do not suggest the presence of mecC MRSA, but highlight the possibility of introducing a simple method in clinical laboratories with high percentage of S. aureus isolates. Conclusion: The implementation of this simple procedure in the laboratory routine is a rapid and economic way to monitoring the presence of mecC MRSA.